Avaliação de aditivos poliméricos e cerâmicos para a otimização microestrutural de refratários semi-isolantes - Farias, Thiago Wisley Barbosa de (2023)
Macroporous insulating refractories have been extensively investigated due to their low thermal conductivity, low density, and non-toxicity compared to fibrous ceramic insulators. However, there are still challenges in adjusting the processing parameters of these materials to obtain microstructures with optimized characteristics. In this context, the present project aimed to evaluate the feasibility of using expanded polymeric microspheres or hollow ceramic microspheres in semi-insulating refractory compositions, with the goal of identifying the most suitable conditions for achieving materials with apparent density of up to 1.7 g/cm3 and thermal conductivity lower than 1 W/m·K in the temperature range between 30 and 800°C. Additionally, to optimize the mechanical strength of the prepared semi-insulating materials, compositions containing calcium aluminate cements or geopolymers as binders were prepared and compared. Formulations based on fused silica were processed and characterized for their rheological, physical, mechanical, and thermal properties. The results indicated that the selected microspheres acted effectively as pore-forming agents, with the polymeric additives promoting the formation of closed pores in the resulting microstructure. In particular, the ceramic containing 0.6 wt.% of polymeric microspheres and a calcium aluminate cement richer in alumina (Secar 71) exhibited the best performance among the studied systems. This castable achieved a flexural strength of 9.21 MPa (after drying at 110°C) and 4.29 MPa (after firing at 815°C), an apparent density of 1.62 g/cm3, and a thermal conductivity of 0.668 W/m·K at 800°C. The semi-insulating materials prepared with geopolymers also demonstrated promising properties, as even in the absence of pore-forming agents, it was obtained refractories with superior flexural strength (surpassing the compositions with cement), an apparent density of 1.68 g/cm3, and a thermal conductivity of 0.735 W/m·K at 800°C.